Evolution of the School Building Network in Portugal in the First Decade of the New Millennium - Carvalho Caseiro, João Pedro (European Public & Social Innovation Review, 2026)
Introduction: The network of non-higher education has evolved in a very peculiar way over the decades in Portugal. The 21st century has been marked by the growth of competitive logic, which also affects the education sector. Even so, this evolution is reflected in different ways in each contexts. Methodology: The research adopted a descriptive quantitative approach, based on statistical data, focused on two regions of Portugal — Coimbra Region and Lisbon Metropolitan Area —, allowing a comparassion from 1999/2000 to 2009/2010. Results: The evolution of non-higher education establishments varies greatly between the two regions under study, although in the country as a whole, private provision has increased and public and total provision has decreased. Discussion: The study provides an interesting and objective analysis of the issue, that should considere a set of considerations, including the evolution of arts and specialized education and vocational education—which were particularly relevant during the period under study—and the emergence of new elements that reinforce the logic of competitiveness in schools, such as the rankings implemented in Portugal since 2001. Conclusions: The different needs of the education system reflect a varied evolution, highlighting territorial asymmetries in the country under study.